Usage of intermingled skin allografts and autografts in a senior patient with major burn injury - Luo Hongmin (De Gruyter, 2021)
Mortality rate in older adults following extensive burn injury is extremely high, and management of these patients is challenging. One of the main problems is that autologous split-thickness skin grafts are scarce and the wounds cannot be covered quickly and effectively. Intermingled skin grafting is a low-tech and economic method, which not only maximizes the use of precious autologous skin but also prevents the wounds from infection and consumption. Herein we present a case of extensive burn injury in a 68-year-old female successfully treated with intermingled skin grafting. The patient was accidentally burned by gas flame, resulting in a major burn injury covering 80% of her total body surface area. Early burn wound excision was performed and the wound was temporarily covered with irradiated porcine skin in the first week after injury. Autologous stamp-like skin grafts were applied to the wound bed 4 weeks after injury. In this operation, the results were not satisfactory. The take rate of the skin grafts is only about 50%. We covered the wounds with intermingled skin allografts and autografts 8 weeks after injury: autografts (0.5 cm × 0.5 cm) + fresh close relative’s allografts (1 cm × 1 cm) + cryopreserved allografts (2 cm × 2 cm).